Pengenalan Ilmu Fiqih pada Anak Usia Dini: Fondasi Spiritualitas Anak yang Kokoh - Wahyudi, Edik; Rohman, Muhammad Muhibbur; Shofi, Muhammad Baba Aidis; Karimah, Latifatul (Yayasan Daarul Huda Kruengmane, 2023)
The importance of Islamic religious education at an early age is the main foundation in shaping children's character. One of the central aspects of religious education is the introduction of the science of jurisprudence. This paper describes an effective approach to introduce the science of jurisprudence at an early age through story books, educational games, and interactive activities. Basic concepts such as prayer, the pillars of Islam, and Islamic etiquette are presented in a fun way and according to children's level of understanding. The bibliography includes sources that can support creative approaches in forming the basis of Islamic faith and character in the early stages of child development. This approach not only enriches religious knowledge, but also forms a solid spiritual foundation from an early age.